The comparative analysis of the economic availability of antihypertensives from the group of beta-blockers in Ukraine - Malanchuk, N. V.; Demchuk, M. B.; Pokotylo, O. O.; Tyzhai, A. B. (Social Pharmacy in Health Care, 2024)
Aim. To conduct comparative studies of the economic availability of beta-adrenergic blocking agents at the domestic pharmaceutical market. Materials and methods. Systematic, comparative, graphic, statistical and marketing research methods were used. The analysis of economic availability of medicines of beta-adrenergic receptor group (ATC code C07) registered in Ukraine in 2022-2024 was performed based on the results of calculation of the average retail price chain index (Ig), the indicator of solvency adequacy (Ca.s.) and the affordability index (D). Results. The highest value of the average retail price chain index for January 2022/2023 and January 2023/2024 for medicines of C07 group of ATC was calculated for carvedilol, atenolol and combinations of atenolol with other diuretics. A slight decrease in the Ig index was recorded for nebivolol, bisoprolol, betaxolol and sotalol. The high Ca.s. index of bisoprolol, carvedilol, atenolol and metoprolol was due to the fact that there were 53 trade names in the Register of Medicines reimbursed under the terms of the “Affordable Medicines” government program. The calculated values of the D index for the drugs studied were greater than one. It is considered acceptable for consumers and determines high economic availability. However, the dynamics of a decrease in the overall affordability index in 2023-2024 compared to 2022-2023 indicates that the growth rate of drug prices exceeded the growth rate of wages. Conclusions. The general trend towards a uniform increase in prices of β-blockers at the domestic pharmaceutical market has been studied. Taking into account the indicator of solvency adequacy and the affordability index, the analysis of the economic availability of the group of medicines studied makes it possible to determine the dynamics of a gradual improvement in the availability of medicines for the population, including due to the successful implementation of the government program for reimbursement of the cost of medicines by budget funds.